Mechanisms of adaptation to intensive loads of 400 meters` hurdles runners at stage of initial basic training - Rovniy, A. S.; Lastochkin, V. M. (Physical Education of Students, 2015)
Purpose: is study of adaptation mechanisms of 400 meter` hurdles-runners to intensive physical loads. Material: in the research 13 - 400 meters` hurdles-runners and 13 - 400 meters` runners participated. Results: it was found that physiological cost of sportsmen`s special workability has fragmentary character. We presented results of physiological and bio-chemical adaptation mechanisms to dozed work. The received results have no confident distinctions and can not objectively characterize mechanisms of sportsmen`s special workability. We did not detect definite differences in indicators of mechanisms, ensuring sportsmen`s special workability under dozed loads. We found, that level of anaerobic glycolysis is an objective criterion of 400 meter` hurdles-runners` special workability. It was shown that for determination of functional potentials for such kind of functioning it is necessary to apply special loads. Conclusions: the received results deepen information about mechanisms of adaptation to specific competition functioning. Correct approaches to processing and analysis of the research`s results permit to more specifically determine sportsmen`s functional potentials in different kinds of competition functioning.